A leucistic female Canis latrans (Carnivora: Canidae) in Costa Rica (UNED Research Journal, 2019)
Partial depigmentation (leucism) is rare in mammals. We report 17 camera trap records of a single female leucistic coyote (Canis latrans) in Costa Rica between 2014 and 2018.
Keywords: coyote; mammal; leucism; camera trap; Costa Rica